Association Between Family Social Support and Emotional Stability Among People with Mental Disorders: A Cross-Sectional Study - Maulidiyah Junnatul Azizah Heru; Faeruza; Tasrip (Genius Journal of Nursing, 2026)
Background: Family social support is an important factor in community mental health care because families are the closest support system for people with mental disorders. Adequate family support may help patients maintain emotional stability and adaptive responses in daily life. Objectives: This study aimed to analyze the association between family social support and emotional stability among people with mental disorders. Methods:  This study used a correlational analytic design with a cross-sectional approach. A total of 110 respondents were selected using purposive sampling. Family social support was measured using a structured questionnaire, while emotional stability was assessed using an observation checklist. Data were analyzed using descriptive statistics and the Chi-square test Results:   Most respondents received moderate family social support (55.0%), and most people with mental disorders showed adaptive emotional responses (59.0%). The Chi-square test showed a significant association between family social support and emotional stability (χ² = 39.885; p < 0.001). Better family social support was associated with more adaptive emotional responses. Conclusions:  Family social support was significantly associated with emotional stability among people with mental disorders. Strengthening family education and supportive home-based care may help improve adaptive emotional responses in community mental health services.